If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -3) + (5x + -5) = 0 Reorder the terms: (-3 + 2x) + (5x + -5) = 0 Remove parenthesis around (-3 + 2x) -3 + 2x + (5x + -5) = 0 Reorder the terms: -3 + 2x + (-5 + 5x) = 0 Remove parenthesis around (-5 + 5x) -3 + 2x + -5 + 5x = 0 Reorder the terms: -3 + -5 + 2x + 5x = 0 Combine like terms: -3 + -5 = -8 -8 + 2x + 5x = 0 Combine like terms: 2x + 5x = 7x -8 + 7x = 0 Solving -8 + 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 7x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + 7x = 0 + 8 7x = 0 + 8 Combine like terms: 0 + 8 = 8 7x = 8 Divide each side by '7'. x = 1.142857143 Simplifying x = 1.142857143
| 3z-4=9 | | x+2+x=210 | | 2j-1=9 | | 9b^4-16=0 | | 7w+4x-4y-x-2w+3y-3x+4w= | | 2x+2=-11 | | 1+6x=7x-4 | | (9x+2)=3x-22 | | 32(x-1)=-8(4x-x)+24x | | 7(x-7)=7x+14 | | (9x+2)=3x-23 | | 12m-12m=2(-12+12m)-12(10-10m) | | 3r-3=6 | | (x-4)(x^2+6x-1)= | | 20y+18x=10-18x | | 0.02(2t-7)=0.04(t+5)-0.34 | | 6.8x+2=5.8x | | m/2-1=11 | | 21=49-4(5-1w) | | 4t^2-52t+160=0 | | 2w+2(2w+6)=28 | | -9+7z+2-5z= | | k=7+9 | | 27=-9(y-5) | | 3m+(m+7n)-(2m+5n)= | | e^5k=32 | | -6u+-u= | | 5(x+1)-3(x-2)=17 | | .2k-(k+.34)=.67(k+3) | | -3(4y+1)-19=-8(y+4)+4y | | 8s+18=6(2s+3)-45 | | 2(2n+2)=7(4n+4)+4 |